Comparative Effectiveness of Dental Anatomy Carving Pedagogy: A Systematic Review. Issue 8 (1st August 2015) - de Azevedo, Renato de A.; da Rosa, Wellington Luiz de O.; da Silva, Adriana F.; Correa, Marcos B.; Torriani, Marcos A.; Lund, Rafael G.
Abstract : The aim of this study was to review the effectiveness of methods used for teaching dental anatomy carving to dental students in operative dentistry as evaluated in published studies. This systematic review is described in accordance with the PRISMA statement. Two independent reviewers performed a systematic literature search of research published from January 1945 until May 2014. Seven databases were screened: MedLine (PubMed), Lilacs, IBECS, Web of Science, Scopus, SciELO, and The Cochrane Library. After removing duplicates, only studies using dental carving to assess the practical knowledge of anatomy were selected. The tabulated data were organized by title of article, names of authors, number of students assessed, assessment method, material used, groups tested, main results, and conclusions. The methodology quality was assessed according to the Cochrane Handbook for Systematic Reviews of Interventions . Initially, 2, 258 studies were identified in all databases. Five articles met the eligibility criteria and were included in this review. According to these studies, the geometric method, teaching step‐by‐step along with the teacher, and adjuvant methods such as the use of tutors and teaching through digital media with DVDs proved to be effective in improving learning. There is no standard technique that is widely accepted for the teaching of dental carving, nor is there an appropriately validated method of evaluation to verify whether the teaching methods used are effective for the acquisition of skills and expertise in dental anatomy by students.